The Use of Albuterol in Young Infants Hospitalized with Acute RSV Bronchiolitis. (26th August 2012) - Del Vecchio, Michael T.; Doerr, Laura E.; Gaughan, John P.
Abstract : Objective . To evaluate the effects of albuterol use in young infants admitted with respiratory syncytial virus (RSV) bronchiolitis with regards to length of time on supplemental oxygen and length of stay (LOS). To consider the possibility that albuterol use may increase the need for supplemental oxygen and increase LOS. Design, Setting, and Participants . Full-term infants between the ages of 11 days and 90 days (N = 316 ) were included in this retrospective study. Infants included were hospitalized with a diagnosis of RSV bronchiolitis at a university-affiliated children's hospital. Results . In 4 of 5 severity groups, patients who received albuterol required more time on supplemental oxygen and had longer LOS. The differences only reached statistical significance in one of the severity groups in regards to LOS. Conclusions . The use of albuterol does not appear to be useful in the treatment of young infants with RSV bronchiolitis and may actually be harmful, in regards to increased supplemental oxygen need.